Predictors of work disability after start of anti-TNF therapy in a national cohort of Swedish patients with rheumatoid arthritis: does early anti-TNF therapy bring patients back to work?. Issue 7 (10th January 2017) - Olofsson, T; Petersson, I F; Eriksson, J K; Englund, M; Nilsson, J A; Geborek, P; Jacobsson, L T H; Askling, J; Neovius, M
Abstract : Objectives: To examine predictors of work ability gain and loss after anti-tumour necrosis factor (TNF) start, respectively, in working-age patients with rheumatoid arthritis (RA) with a special focus on disease duration. Methods: Patients with RA, aged 19–62 years, starting their first TNF inhibitor 2006–2009 with full work ability (0 sick leave/disability pension days during 3 months before bio-start; n=1048) or no work ability (90 days; n=753) were identified in the Swedish biologics register (Anti-Rheumatic Treatment In Sweden, ARTIS) and sick leave/disability pension days retrieved from the Social Insurance Agency. Outcome was defined as work ability gain ≥50% for patients without work ability at bio-start and work ability loss ≥50% for patients with full work ability, and survival analyses conducted. Baseline predictors including disease duration, age, sex, education level, employment, Health Assessment Questionnaire, Disease Activity Score 28 and relevant comorbidities were estimated using Cox regression. Results: During 3 years after anti-TNF start, the probability of regaining work ability for totally work-disabled patients was 35% for those with disease duration <5 years and 14% for disease duration ≥5 years (adjusted HR 2.1 (95% CI 1.4 to 3.2)). For patients with full work ability at bio-start, disease duration did not predict work ability loss. Baseline disability pension was also a strong predictor of work ability gain after treatment start. Conclusions: A substantial proportion of work-disabled patients with RA who start anti-TNF therapy regain work ability. Those initiating treatment within 5 years of symptom onset have a more than doubled 3-year probability of regaining work ability compared with later treatment starts. This effect seems largely due to the impact of disease duration on disability pension status.